More than supportive: liana attachment to supports lead to profound changes in xylem anatomy, hydraulic conductivity and cambium transcroptional profile - Lima, André Carvalho (2020)
o Secondary xylem performs two crucial functions, namely mechanical support and water and mineral conduction. Many lianas show two contrasting xylem anatomy phases, the initial homogeneous, fibrous and small vesselled self-supporting xylem, and the later lianescent xylem, which is anatomically complex, with large and dimorphic vessels and less supportive tissue. It is not known, however, what leads to the abrupt change of xylem formation. o In this study, we address the question of what triggers and which are the genetic determinants of the profound changes during the transition from self-supporting to the lianescent xylem in the liana Bignonia magnifica, Bignoniacae. For this purpose, we first analyzed growth rates of plants grown with and without supports, how hydraulic parameters varied along the stem and described in detail self-supporting and lianescent xylem anatomy. We then constructed cambium and differentiating xylem transcriptome of these two phases and conducted a differential expression analysis of RNA-Seq generated data. o Our work shows that the presence of supports leads to changes in growth pattern and anatomical parameters along the stem, increasing potential conductivity, and promotes lianescent xylem formation. These changes are associated to differential expression of genes related to cell division and cell wall biosynthesis, overregulated in self-supporting phase, and of transcription factors, defense/cell death, and hormone-responsive genes, overregulated in lianescent phase. o We conclude that the more complex anatomy in lianescent phase is the result from a more complex transcriptional regulation in cambium and wood forming tissues